(untitled) (Plant Tissue Culture and Biotechnology, 2013)
In vitro propagation system has been developed for an important ornamental and medicinal plant, Muscari armeniacum Leichtil. ex Bak. A range of a cytokinin and auxin concentration has been investigated for axillary bulblet proliferation, and direct and indirect adventitious bulblet regeneration from the explants whole bulb, one fourth part of bulb, bulb-scale of ex vitro (field grown mature bulb), and only leaf-sheath explants of in vitro grown bulblet. Axillary bulblet regeneration occurred on MS containing 2.0 - 8.0 ?M BAP or Kn. Direct adventitious bulblets were induced successfully on MS basal medium supplemented with various concentrations of BAP or Kn (1.0 - 4.0 ?M) in combi-nation of either NAA, IBA, or 2,4-D (0.5 - 4.0 ?M). The maximum frequency of adventitious bulblets regeneration occurred from both bulb-scale and leaf-sheath explants on MS with 4.0 ?M BAP and 2.0 ?M NAA, IBA, or 2,4-D. The highest frequency (95.5%) of indirect adventitious bulblets was obtained from in vitro grown leaf-sheathderived callus on MS containing 4.0 ?M BAP with 1.0 ?M 2,4-D whereas, highest number (80.2) and average length (55.5 cm) of bulblets were obtained on MS supplemented with 4.0 ?M BAP and 1.0 ?M NAA. In vitro grown bullets was rooted successfully on MS with 0.5 - 4.0 ?M of IBA, NAA, or IAA. The rooted bulblets were transferred to garden soil and successfully established under ex vitro environment. DOI: http://dx.doi.org/10.3329/ptcb.v22i2.14200 Plant Tissue Cult. & Biotech. 22(2): 113-126, 2012 (December)